Family support and rheumatoid arthritis management in Lamongan: A mixed-methods study - Unif, Dian Saputran; Sitiawari, Wulan (Indonesian Nursing Journal, 2025)
Background: Rheumatoid arthritis (RA) is a chronic autoimmune disease that significantly impacts patients' physical, psychological, and social well-being. In rural areas like Lamongan, Indonesia, family support plays a crucial role in managing RA due to limited access to healthcare services and cultural emphasis on familial care. However, the dynamics of family support and its influence on RA outcomes remain underexplored. Purpose: This study aimed to examine the influence of family support on disease management and patient outcomes among individuals with RA in Lamongan. Methods: A mixed-methods approach was employed, involving 120 RA patients for the quantitative component and in-depth interviews with 15 patients and their caregivers for qualitative insights. The Family Support Scale and Rheumatoid Arthritis Impact of Disease (RAID) questionnaire were used to assess family support and disease impact, respectively. Quantitative data were analyzed using descriptive and inferential statistics, while thematic analysis was applied to qualitative data. Results: The results revealed a significant negative correlation between family support and RAID scores (r = -0.68, p < 0.01), indicating that higher levels of family support are associated with reduced disease impact. Emotional support emerged as the most impactful dimension, significantly improving mental health outcomes. Qualitative findings highlighted the central role of cultural norms in shaping family caregiving practices, which provided robust support but sometimes led to patient dependency. Conclusion: Family support plays a pivotal role in RA management, underscoring the need for family-centered interventions that address emotional and practical needs while mitigating caregiver burden. Future strategies should integrate culturally sensitive approaches and enhance access to healthcare resources to optimize outcomes for RA patients in similar rural settings.